Identification of genomic regions related to lipid and cholesterol content in beef - Rezende, F. M.; Oliveira Junior, G. A.; Carvalho, M. E.; Ventura, R. S.; Ferraz, J. B. S.; Eler, J. P. (Cuban Journal of Agricultural Science, 2016)
The aim of this study was to identify genomic regions that potentially have association with lipid and cholesterol content in Nellore cattle meat. Phenotypes of 615 Nellore bulls were obtained according to the methods described by Bligh and Dyer (1959) and Saldanha et al. (2004). Data of 658 genotyped Nellore bulls were used for association studies through the ssGWAS method. Those animals were genotyped with the Illumina Bovine HD® Beadchip (777 962 SNP) or Gene Seek GGPi (74,153 SNP). Based on another Nellore population genotyped for Illumina Bovine HD® Beadchip, genotypes were determined using the FImpute software. After quality control (MAF <2% and call rate <90%), 535 824 SNP in autosomal chromosomes were used in the association analyses. Single step analyses were performed using a pedigree composed by 4065 animals by the BLUPf90 program considering windows of 10 markers to estimate their effects. This procedure enables the identification of regions associated with lipid and cholesterol content by chromosome. Results of this research showed regions on chromosomes 5, 10, 12 23 and 29 related to lipid content and on chromosomes 3, 10, 11, 12 13, 17 and 18 associated with cholesterol deposition. Key-words: GWAS, Nellore, meat quality, SNP.